A 21-plex DIP panel's application in multinational Chinese population. (December 2015) - Jiang, Youjing; Wang, Li; Li, Zhilong; Zhu, Jing; Peng, Duo; Su, Qin; Mao, Jiong; Wang, Hui; Liang, Weibo; Zhang, Lin
Abstract: DIPs (insertion/deletion polymorphisms) combining the advantages of both SNPs (single nucleotide polymorphisms) and STRs (short tandem repeats) show a great value in forensic case works. A high sensitive 21 AIM (ancestry informative markers)-DIPs panel developed by Daniel et al. is sufficient to distinguish between three major global population groups. However, Chinese population was not included in Daniel's research. In this study, DNA samples from three Chinese population groups living in west of China (Han ( n = 60), Uighur ( n = 60) and Tibetan ( n = 60)) were extracted and analyzed following Daniel's procedure. The difference in biogeographic ancestry between the three Chinese population groups was compared. The consequence shows no significant difference between Chinese Han, Uighur and Tibetan populations. In summary, this 21-plex DIP panel is unable to distinguish the three Chinese populations. To characterize three groups in China, more AIM-DIPs are needed.